2015
DOI: 10.1109/tia.2015.2422825
|View full text |Cite
|
Sign up to set email alerts
|

High-Resistance Grounded Power System

Abstract: To minimize ground fault during a line-to-ground fault condition, it has been a common practice to use highresistance grounded (HRG) power systems, both at low voltage (LV) and at medium voltage (MV). The criteria for designing HRG systems are very well known to the industry; however, the opinions of industry experts have been divided on limiting the use of HRG systems for MV systems to voltages of less than 4.16 kV and phase-ground fault currents of less than 10 A without clarifying that it applies to systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The HRG method effectively suppresses the fault current on the line, preventing overvoltage and ensuring the safety of personnel and equipment. The HRG method requires ensuring that the fault current is equal to or slightly higher than the system charging current [24,35,36]. In Section 6.2.3 of IEEE 80005-1, the fault current generated by the impedance should be at least 1.25 Two types of NGRs (R N ) are commonly used: HRG and LRG.…”
Section: Hvsc Grounding (Earthing) Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…The HRG method effectively suppresses the fault current on the line, preventing overvoltage and ensuring the safety of personnel and equipment. The HRG method requires ensuring that the fault current is equal to or slightly higher than the system charging current [24,35,36]. In Section 6.2.3 of IEEE 80005-1, the fault current generated by the impedance should be at least 1.25 Two types of NGRs (R N ) are commonly used: HRG and LRG.…”
Section: Hvsc Grounding (Earthing) Systemmentioning
confidence: 99%
“…The HRG method effectively suppresses the fault current on the line, preventing overvoltage and ensuring the safety of personnel and equipment. The HRG method requires ensuring that the fault current is equal to or slightly higher than the system charging current [24,35,36]. In Section 6.2.3 of IEEE 80005-1, the fault current generated by the impedance should be at least 1.25 times the system charging current, with a value exceeding 25 A-5 s. However, the same shore power system paired with different ship types and electrical architectures can result in varying system charging currents [32].…”
Section: Hvsc Grounding (Earthing) Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional arc-optic grounding fault identification method of the distribution network is based on the steadystate or transient electrical parameters and the set threshold (Chen et al, 2021), and in the fault identification method based on the transient electrical parameters, the characteristic parameters of the typical fault type are first extracted, including wavelet transform (WT) (Qin et al, 2018;Lin et al, 2019;Wei et al, 2020a), empirical mode decomposition (EMD) (Guo et al, 2019;Cai and Wai, 2022), and S transformation (ST) (Peng et al, 2019); Then, the arc ground fault is classified and identified by the pattern recognition method, mainly including the neural network method (Siegel et al, 2018;Du et al, 2019a), the Support Vector Machine (SVM) (Xia et al, 2019;Dang et al, 2022), the fuzzy control method (Zeng et al, 2016), the clustering (Wang et al, 2015), etc., in addition, the high-precision current transformer can be used to improve the fault identification ability (Paul, 2015), but the detection cost is also significantly increased.…”
Section: Introductionmentioning
confidence: 99%